2016
DOI: 10.1007/s12928-016-0444-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation for the efficacy and safety of the crosser catheter as a CTO crossing device and a flossing device

Abstract: The Crosser catheter is a unique device that facilitates antegrade intraluminal recanalization by high-frequency vibration energy and cavitation. We used this device not only as a chronic total occlusion (CTO) crossing device, but also as a flossing device in stenotic lesions and we also evaluated the efficacy of this device when used with both the "Crosser preceding" and the "Guidewire preceding" in CTOs. Complications related to this device were investigated, too. We retrospectively analyzed a total of 90 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 4 publications
0
13
1
Order By: Relevance
“…They also demonstrated that a Proposed Peripheral Arterial Calcium Scoring System grade of 4 was a predictor of these complications. 4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also demonstrated that a Proposed Peripheral Arterial Calcium Scoring System grade of 4 was a predictor of these complications. 4…”
Section: Discussionmentioning
confidence: 99%
“…1 –3 Recently, the detachment and complete separation of the tip of the Crosser catheter was reported as a serious complication of the Crosser system. 4 However, there is limited information on bailout methods for this complication. Here, we describe a case of successful retrieval of the separated tip of a Crosser catheter using a 2-wire technique with a gooseneck snare.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in endovascular therapy (EVT) devices have reported effectiveness of EVT for CFA 2 . Some reports have shown that balloon dilation enlarges the lumen by passing multiple wire routes within calci ed plaques 3 . However, it is not easy to pass guidewire through hard plaque.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several EVT techniques for removing calci ed lesions, such as the crossbow technique (Crosser® supported by a bent 0.014-in wire) [4] and Pierce technique (percutaneous direct needle puncture of the calci ed plaque) [5], have been reported. However, these techniques have shown a limited ability in reducing calcium volume.…”
Section: Introductionmentioning
confidence: 99%